2006
DOI: 10.1093/protein/gzl033
|View full text |Cite
|
Sign up to set email alerts
|

Human monoclonal antibodies to domain C of tenascin-C selectively target solid tumors in vivo

Abstract: We had previously reported that splice isoforms of tenascin-C containing the extra-domain C are virtually absent in normal adult tissues but are highly abundant in high-grade astrocytomas, with a prominent peri-vascular pattern of expression. We now report that the extra-domain C of tenascin-C is strongly expressed in the majority of lung cancers, with a vascular and stromal pattern of expression. Using antibody phage technology, we have generated a human monoclonal antibody (G11), with a dissociation constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 14 publications
1
72
0
2
Order By: Relevance
“…Interestingly, tenascin C splice isoforms are commonly found in the tumour stroma and/or around tumour blood vessels [92][93][94][95][96][97][98] and serve as markers of angiogenesis 99 . The regulation of alternative splicing of tenascin C is complicated by the observation that the extra domain C displays a more restricted pattern of expression than the other domains between A1 and D 100,101 . However, whenever this domain is inserted into the tenascin C molecule (for example, in high-grade astrocytomas), it tends to accumulate around neovascular tumour structures [100][101][102] .…”
Section: Sulphonamides As Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, tenascin C splice isoforms are commonly found in the tumour stroma and/or around tumour blood vessels [92][93][94][95][96][97][98] and serve as markers of angiogenesis 99 . The regulation of alternative splicing of tenascin C is complicated by the observation that the extra domain C displays a more restricted pattern of expression than the other domains between A1 and D 100,101 . However, whenever this domain is inserted into the tenascin C molecule (for example, in high-grade astrocytomas), it tends to accumulate around neovascular tumour structures [100][101][102] .…”
Section: Sulphonamides As Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%
“…The regulation of alternative splicing of tenascin C is complicated by the observation that the extra domain C displays a more restricted pattern of expression than the other domains between A1 and D 100,101 . However, whenever this domain is inserted into the tenascin C molecule (for example, in high-grade astrocytomas), it tends to accumulate around neovascular tumour structures [100][101][102] . The A1 domain of tenascin C is the target of the F16 antibody, whereas the 81C6 antibody recognizes domain D.…”
Section: Sulphonamides As Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%
“…This study found strong associations of FNIII-C with high grade astrocytoma and glioblastoma, cerebral cavernomas and lung cancers where the distribution of FNIII-C was consistently associated with tumor stroma, tumor blood vessels and proliferating cells in these tissues. [116][117][118] Likewise, FNIII-B containing tenascin-C isoforms co-localize to laminin-5/g2 in the basement membrane region of oral SCC, where increased expression positively correlates with malignancy grade. 119 Another study revealed by IHC and RT-PCR that invasive urothelial cell carcinoma (UCC) exhibits restricted expression of FNIII-A1/ B or D which is closely associated with tumor blood vessels, invasive tumor stroma and damaged muscle.…”
mentioning
confidence: 99%
“…Antigens that are preferentially expressed in the tumor extracellular matrix may be better suited for tumor-targeting applications. In fact, several groups have demonstrated that antibodies specific to components of the extracellular matrix (EDB domain of fibronectin (41), domain C of tenascin C (42), and laminin (6,33)) were capable of selective targeting of neovascular structures in solid tumors. However, it has been shown that antibodies against tumor-associated vascular 8 and L36).…”
Section: Discussionmentioning
confidence: 99%